Enhancing Patient Safety Culture in Hospitals: A Comprehensive Approach - Aisha Ali Ali Shami,; Hessa Abdullah suliman alhusika,; Nadia salem Alshahrani,; Sana Faiz albishi,; Falaa Mohammed Alahmari,; Maha Saleh Bafeel,; Wardah Abdullah Eed Alrwaily,; Ghadah Hamzah Bukhari,; Khalda fahad alshammari,; Turkiaha Dakhheal AL Harbi,; Ameera Mohamed Asiri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Patient safety culture is a critical aspect of healthcare quality, directly impacting patient outcomes and healthcare delivery. This paper provides an in-depth examination of the concept of patient safety culture, its dimensions, and strategies for enhancing it in hospital settings. Drawing from a comprehensive review of the literature, we explore the multifaceted nature of patient safety culture, encompassing leadership commitment, teamwork, communication, error reporting, continuous learning, and patient engagement. The paper highlights the significance of fostering a non-punitive environment that encourages open dialogue, promotes systems-based thinking, and prioritizes continuous quality improvement. Furthermore, we discuss the role of healthcare professionals, particularly nurses, as pivotal agents in cultivating a robust patient safety culture. The paper also addresses the challenges and barriers to implementing patient safety initiatives, such as resistance to change, resource constraints, lack of standardization, and cultural barriers. To overcome these obstacles, we provide practical recommendations for healthcare organizations, including leadership accountability, comprehensive staff education and training, encouraging open communication and feedback, promoting teamwork and interprofessional collaboration, engaging patients and families, adopting a continuous quality improvement approach, and leveraging technology and data analytics. By embracing a multi-faceted and collaborative approach, hospitals can create a culture that prioritizes patient safety, fosters continuous learning, and drives excellence in healthcare delivery.